EXPERIENCE WITH LIGHT DYNAMIC PENETRATION IN A LANDSLIDE LOCALITY - ŠIROKÝ, Tomáš; ŠANCER, Jindřich (GeoScience Engineering, 2019)
Because of vital prevention and redevelopment measures in problem localities affected by slope instability, geotechnical investigations must be carried out. One of the applicable methods is Light Dynamic Penetration (LDP). Although it was designed for easy field investigations in planning line structures to identify parameters, such load bearing capacity, and compactness, its use proves to be much wider. Using LDP it is possible to detect the interfaces between the discrete layers, potential slip surfaces, or groundwater level. However, it is important to note that the results of LDP are always related to one point only and to investigate a whole area, a complementary survey is needed. In the paper we report research where we used a geophysical method of Electrical Resistivity Tomography (ERT) to validate the results rendered by Light Dynamic Penetration in a redeveloped post-mining locality characteristic of landslides. The results of both measurement methods were unified for better interpretation and clarification to find out whether LDP is suitable to investigate a landslide locality. It shows that LDP provides relevant information on the massif structure in a given locality, but as opposed to other geophysical methods LDP informs only about one point only. The authors thus recommend carrying out surveys in landslide areas combining LDP and ERT as complementary measurements of groundwater level in the openings made using LDP. Mutually combining these two methods, it is possible to obtain a number of valuable information on landslide conditions (depth and course of shear plane, groundwater level, structure of layers, etc.) and physical - mechanical properties of soils. Keywords: Light Dynamic Penetration, Slope instability, Electrical Resistivity Tomography DOI 10.35180/gse-2019-0017